KONSTRUKSI HAJI MISBACH SEBAGAI ANCAMAN DALAM PERS KOLONIAL HINDIA BELANDA (1924) - Bella Riskika Taufik; Iin Isnaini (FASTABIQ: JURNAL STUDI ISLAM, 2026)
A This article aims to analyze how Haji Mohammad Misbach was represented as a threatening figure in colonial discourse through coverage in the newspaper Algemeen Handelsblad voor Nederlandsch-Indië in 1924. This study departs from the limitations of previous research that tended to place Misbach within a historical, political, and ideological framework, without specifically examining the process of constructing his image in colonial media. This research utilizes historical methods combined with a discourse analysis approach, using the text "De Interneering van Hadji Misbach" as the primary source. The analysis focuses on identifying the diction choices, narrative structure, and representational patterns used to frame Misbach's figure. This study uses a discourse analysis approach to examine the construction of Haji Misbach's representation in the colonial press. The results show that Misbach's representation as a stokebrand (dangerous instigator) is not neutral, but rather a discursive construction produced through strategies of labeling, stereotypical repetition, and narrative framing. This construction served to shape public perception and legitimize the colonial government's repressive policies, including the practice of interning, as rational measures to maintain public order. These findings confirm that the colonial press served not only as a medium of information but also as an instrument of power in producing meaning and controlling discourse on Islam and social resistance in the Dutch East Indies. This article contributes to broadening the study of social and intellectual history by emphasizing the importance of representational analysis in understanding the relationship between language, power, and colonialism.